2013
DOI: 10.4314/ijbcs.v7i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Gastro-entérites en milieux des réfugiés au Tchad

Abstract: ; Tel : +235 66 37 36 47 / +235 90209073 RESUME Les réfugiés et déplacés de guerre sont des personnes vulnérables. C'est pourquoi, nous avons entrepris une étude des gastro-entérites dans leurs milieux au Sud et à l'Est du Tchad. Cette étude a concerné 53 patients dans les camps du Sud dont 28,30% sont des enfants de 0 à 5 ans. Elle a été couplée d'une enquête sur l'état nutritionnel de 205 réfugiés dans les deux zones. L'isolement et l'identification des entéropathogènes dans les selles ont été réalisés au la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…This is because money is dirty and can contaminate safe food . Several studies have shown that hands carry most of the time faeces contamination germs that are often responsible for diarrheal diseases and gastroenteritis (Baba-Moussa et al, 2006;Bessimbaye et al, 2013). Other research has found that slicers and cutters are recognized as important vehicles for the contamination of cooked meat products both in the factory and at the point of sale (Pérez-Rodriguez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because money is dirty and can contaminate safe food . Several studies have shown that hands carry most of the time faeces contamination germs that are often responsible for diarrheal diseases and gastroenteritis (Baba-Moussa et al, 2006;Bessimbaye et al, 2013). Other research has found that slicers and cutters are recognized as important vehicles for the contamination of cooked meat products both in the factory and at the point of sale (Pérez-Rodriguez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They are also accessible in unity, and at affordable cost. In addition, Bessimbaye et al (2013) point out that the increase in resistance is due to abusive and inappropriate prescription by health workers. For Armengaud et al (1994), beta-lactam-resistant bacteria produce beta-lactamases that modify or inactivate antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic bacteria and viruses can cause many eating disorders. Tese pathogens include Escherichia coli, Shigella spp., Salmonella spp., Staphylococcus aureus, Vibrio cholerae, Streptococcus spp., Bacillus cereus, Yersinia enterocolitica, Campylobacter spp., Listeria monocytogenes, and Clostridium perfringens [9]. A good understanding of the nutritional quality and microbial diversity of cereal-based fermented porridges in northern Benin would be a prerequisite for developing and implementing evidence-based policies to improve food and nutrition security and have a standardized process.…”
Section: Introductionmentioning
confidence: 99%
“…Many pathogenic bacteria and viruses have been identified as responsible agents for these eating disorders. These are Escherichia coli , Shigella spp., Salmonella spp., Staphylococcus aureus , Streptococcus spp., Vibrio cholerae , Bacillus cereus , Campylobacter spp., Yersinia enterocolitica , Clostridium perfringens and Listeria monocytogenes [9]–[11]. Others have noted the presence of mold producing carcinogenic toxins such as aflatoxins in corn, millet, sorghum, peanuts, sesame, soya etc.…”
Section: Introductionmentioning
confidence: 99%